Diseño y construcción de un sistema de automatización de un destilador eléctrico para la obtención de aceite esencial - López Robles, Cristina Dayanara (2018)
Abstract:The present work proposes the design and construction of an automation system of an electric distiller for obtaining essential oils; defining the temperature and liquid level as control variables, as a consequence the system was composed by the following elements: temperature sensor RTD Pt100, a float level sensor, an expansion module, a PLC, a solenoid valve and a solid state relay that commutes the power pass to the electrical resistance, responsible for increasing the temperature inside the distillation process. For the water level control in the boiler an on-off system was defined while a PI controller for the temperature control, whose variables were fixed by experimental tests, showing better results in the experimentation the Callender method with a settling time of 3.75 min, P.O=0, Ess= 1 oC and when introducing perturbations a time of 1.25 minutes to retake the settling. KEY.